Negotiating New Territory: Indian Jewish Women and Families in Toronto - Amanda Kelly Train (Canadian Jewish Studies, 2018)
This article explores the obstacles that Indian Jewish women faced in the immigration and settlement process in Toronto between 1964 and 1980. I argue that the feminization of domestic labour created new and unforeseen challenges for Indian Jewish women in family life in the aftermath of arriving in Toronto. These challenges reflect not simply that they became solely responsible for the mundane performance of domestic labour and childcare, but also the importance of these tasks in maintaining Indian Jewish culture and identity within the family.